2020
DOI: 10.3174/ajnr.a6859
|View full text |Cite
|
Sign up to set email alerts
|

Neck Location on the Outer Convexity is a Predictor of Incomplete Occlusion in Treatment with the Pipeline Embolization Device: Clinical and Angiographic Outcomes

Abstract: BACKGROUND AND PURPOSE: With the increasing use of the Pipeline Embolization Device for the treatment of aneurysms, predictors of clinical and angiographic outcomes are needed. This study aimed to identify predictors of incomplete occlusion at last angiographic follow-up. MATERIALS AND METHODS:In our retrospective, single-center cohort study, 105 ICA aneurysms in 89 subjects were treated with Pipeline Embolization Devices. Patients were followed per standardized protocol. Clinical and angiographic outcomes wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…Platelet function testing was routinely performed using the VerifyNow P2Y12 assay and the VerifyNow Aspirin assay (Accumetrics, San Diego, California, USA) on the day before. Antiplatelet medications were adjusted accordingly, as in previous reports 15. Dual antiplatelet therapy was continued for at least 6 months after the procedure, and single antiplatelet therapy was continued indefinitely thereafter.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Platelet function testing was routinely performed using the VerifyNow P2Y12 assay and the VerifyNow Aspirin assay (Accumetrics, San Diego, California, USA) on the day before. Antiplatelet medications were adjusted accordingly, as in previous reports 15. Dual antiplatelet therapy was continued for at least 6 months after the procedure, and single antiplatelet therapy was continued indefinitely thereafter.…”
Section: Methodsmentioning
confidence: 99%
“…Heparin anticoagulation was implemented throughout the procedure. Flow diversion treatment was performed using standard technique, as described previously 15 16…”
Section: Methodsmentioning
confidence: 99%
“…This location of the aneurysm with respect to the parent vessel has been identified as less favourable for successful embolization of the sac after FDS treatment (Sunohara et al. 2021). A study comparing the clearance of aneurysmal sac on the outer convexity versus the concave side of the parent vessel also observed significantly faster clearance for the aneurysm on the outer convexity (Epshtein & Korin 2018).…”
Section: Comparison Of Haemodynamics Before and After Fds Treatmentmentioning
confidence: 99%
“…After having analysed the geometry and the outcomes after treatment with flow-diverting stents (FDS) of 105 aneurysms, Sunohara et al. (2021) concluded that an aneurysm neck located on the outer wall of the curved artery is a predictor for incomplete occlusion after treatment. Additionally, numerical simulation of 23 patient aneurysms (Larrabide et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation